In vitro‐studies of adenosine‐ β‐cyclodextrin inclusion complexes loaded into chitosan, sodium alginate and bentonite‐based nanocomposite optimized by RSM as a sustained release system. Issue 31 (3rd June 2022) - Khushbu,; Jindal, Rajeev
Abstract: Drugs with less aqueous solubility and permeability acquire significant hurdles in designing safe and effective formulations. The purpose of this study was to prepare an adenosine (ADS): β‐cyclodextrin (β‐CD) inclusion complex that could be consistently incorporated into a nanocomposite system for topical administration. Several procedures, including kneading, microwave irradiation, and co‐precipitation, were used to develop an adenosine: β‐CD inclusion complex. ROESY, DSC, XRD, and 1 H NMR spectroscopy were used to analyze the adenosine‐β‐CD inclusion complex. Then bentonite (BN) incorporated chitosan (CH) and sodium alginate (ALG) nanocomposite were synthesized by microwave irradiation method. Response Surface Methodology (RSM) design was executed to optimize the reaction parameters. The Minimum Resolution V design was implemented to find significant variables to get maximum percentage swelling. The inclusion complexes of ADS: β‐CD were directly loaded into the CH/ALG/BN nanocomposite and the adenosine release was analyzed in simulated intestinal fluids (SIF) and simulated gastric fluids (SGF). Five kinetic models were investigated to know about the drug release mechanism. After a 24‐h interval, the ADS final release was 86 ppm at pH 2, 96 ppm at pH 7, and 85 ppm at pH 7.4. Bentonite has a layered structure that allows it to introduce the drug molecule into its cavity, resulting in sustainable adenosine release. The exploratory kinetic analysis demonstrated that β‐CD influences polymer relaxation, resulting in slow release. Abstract :